Adoption of climate smart technologies in East Africa: Findings from two surveys and participatory exercises with farmers and local experts - Bedmar Villanueva, Ana; Jha Y; Ogwal-Omara, Richard; Welch, Eric W.; Seyoum Wedajoo A; Halewood, Michael (2016)
As part of the “Policy Action for Climate Change Adaptation” (PACCA) project this info note summarizes findings of a project activity entitled “Influencing and linking policies and institutions from national to local level for the development and adoption of climate‐resilient food systems in East Africa” undertaken by researchers from Bioversity International and Arizona State University. By conducting a network analysis and participatory exercises with district officials and farmers, the study assesses the extent to which farmers are adopting agricultural practices and correlates the findings about the size and “make up” of the networks in which the farmers are embedded.